2011
DOI: 10.1093/jscr/2011.9.8
|View full text |Cite
|
Sign up to set email alerts
|

Incidentally detected squamous cell carcinoma in non-functioning kidney presenting as multi-cystic mass

Abstract: Squamous cell carcinoma (SCC) of urinary tract is a rarely encountered tumor. The incidence of this tumor is 1.4 per cent of all renal malignancies (1). We present a case of 52 years male with squamous cell carcinoma of renal pelvis, presenting as chronic pyelonephritis transforming the kidney into non-functioning multicystic cavitatory mass without any renal calculi. The case highlights the rarity of tumor in absence of calculi or any other predisposing factor. Moreover, histology of resected specimen detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…There are several reports published on bladder stones and SCC (15,16), although SCC associated with kidney stones appears to be less frequent (17). This may be due to the lack of stasis in the renal pelvis compared to the bladder (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports published on bladder stones and SCC (15,16), although SCC associated with kidney stones appears to be less frequent (17). This may be due to the lack of stasis in the renal pelvis compared to the bladder (18).…”
Section: Discussionmentioning
confidence: 99%
“…Mathur et al (17) reported a case of renal SCC presenting as a multicystic mass. Verma et al (20) presented a case of SCC and kidney stones and reported the low incidence of this tumor in non-functioning kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…It usually occurs in late adulthood and is reported of an equal incidence in men and women [ 5 ]. However, according to the recent literatures (Table 1 ), men bear a higher incidence of renal SCC, probably because of higher incidence of nephrolithiasis in men [ 2 , 6 20 ]. Long-standing nephrolithiasis and/or chronic pyelonephritis are the most common causes for renal SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several stressors were reported to induce this malignant transformation and include nephrolithiasis, chronic urinary tract infection, renal tuberculosis, radiation therapy, percutaneous nephrostomy, immunosuppression, schistosomiasis, and vitamin A deficiency. Of these, the main risk factor almost constant in all reported cases of SCC of the renal pelvis is a history of long standing nephrolithiasis [ 6 , 7 ]. Due to the rarity of the SCC of the renal pelvis and the high occurrence of kidney stones in the general population, clear recommendations for follow-up of patients with history of nephrolithiasis seem too difficult to achieve.…”
Section: Discussionmentioning
confidence: 99%